PENGARUH PENERAPAN MODEL PEMBELAJARAN CIRCUIT LEARNING TERHADAP HASIL BELAJAR IPS (Studi Eksperimen Kuasi Siswa Kelas III SDN 56 Pekanbaru) - Febria, Danti; Lazim N, Lazim N; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This quasi experiment research aims to describe the influence of the application of learning circuit learning model to the learning outcomes of IPS students of class III SDN 56 Pekanbaru. The design of this study using nonequivalent control group design. Subjects in this study were grade IIIB SDN 56 Pekanbaru as a control class and students of class IIIA SDN 56 Pekanbaru as experimental class. The data collected is the result of IPS learning. The data collected were analyzed by using T test. From the analyzed data obtained t arithmetic = 0.734 and t table = 2.020. Based on the results of this study can be concluded that there is no influence of the application of learning circuit learning model to the results of learning IPS students class III SDN 56 Pekanbaru.Keyword : Circuit learning model, result of learning social science